Parent Education and Future Transition to Cigarette Smoking: Latinos' Diminished Returns - Assari, Shervin; Boyce, Shanika; Caldwell, Cleopatra H.; Bazargan, Mohsen (Frontiers in Pediatrics, 2020)
Background. High parent education is protective against youth health risk behaviors such as tobacco use. According to the Minorities’ Diminished Returns theory, however, higher parental education is less protective for ethnic minority groups relative to the majority group. Objectives: To explore ethnic differences in the effects of parent education on the transition to cigarette smoking in a national sample of American adolescents. Methods. This longitudinal study used data of wave 1 and wave 4 of the Population Assessment of Tobacco and Health (PATH 2013-2018). This analysis included 5,021 American youth who were never smokers at baseline (2013) and were followed for 4 years. The dependent variable was the transition to cigarette smoking. The independent variable was parent education. Youth age, youth gender, parental marital status, and region were the covariates. Ethnicity was the moderating variable. Results. From the 5,021 American youth who were never smokers at baseline (2013), 4490 (89.4%) continued as never smoker and 531(10.6%) became ever smoker. Overall, a higher parent education was associated with a lower likelihood of transitioning to ever and current cigarette smoker at the end of the 4th year. Parent education showed significant interactions with Latino ethnicity on both outcomes suggesting smaller protective effects of parent education on youth tobacco outcomes for Latino than for non-Latino youth. Conclusions. For American youth, ethnicity alters the magnitude of the effect of parent education on the future transition to tobacco use. While overall high parent education is protective against smoking overall, non-Latino Whites (the most socially privileged group) gain most and Latino youth (the least socially privileged groups) gain least from such resources. In addition to addressing low SES, researchers and policymakers should identify and address mechanisms by which high SES minority youth remain at risk of tobacco use.